Body composition and dietary patterns in professional and amateur bodybuilders - Makiel, Karol; Suder, Agnieszka; Kasza, Sebastian; Kubasiak, Katarzyna (Anthropological Review, 2020)
Significant factors affecting body composition and consequently professional and amateur bodybuilders’ performance are both training loads and diet. The aim was to assess dissimilarities in anthropometrical traits and body composition between males practicing bodybuilding professionally and as amateurs, considering their diet and training. The study comprised 55 athletes, i.e. 29 professionals attending national championships and 26 amateur bodybuilders. All participants underwent anthropometric measurements involving body height, waist, arm and thigh circumferences and skinfolds covering trunk and extremities. The original nutritional behavior questionnaire and a 24-hour survey were used. An electronic scale was used to measure body weight and body composition was analyzed with the BIA method. In statistical analysis, the Shapiro-Wilk (W-test), t-student and Mann-Whitney U test were applied. An adipose tissue, assessed on the basis of skinfolds was significantly lower in professionals (p<0.05), whereas lower mean values of body fat free mass (FFM) were found in amateur bodybuilders (p<0.01). Diet survey presented differentiation both in the amount of consumed protein in the diet (1.98 g/kg), in its percentage participation in the diet (21.2%) in favor of the professionals (p<0.05). Significant differentiation was between the groups in the amount of consumed fats (p<0.05). In case of resistance trainings time, energy expenditure and number of trainings were higher for professionals (p<0.05). Bodybuilders feature better developed muscle mass of extremities and a smaller share of percentage of fat mass in body composition in comparison to amateurs. Professional bodybuilders consume proper amount of carbohydrates and fats and significantly higher level of protein, fiber and energy in diet compared to amateur group. In contrary, higher intake of fats is typical for amateur bodybuilders.